?PARTICIPATIVE TRANSFER OF TECHNOLOGY: MEETING THE EMERGING CHALLENGE OF R&D COMMERCIALIZATION IN PAKISTAN (Biological Sciences - PJSIR, 1996)
Restrictive public sector funding to R&D with the expectation of greater participative investment by the end-users has led to the emergence of "third generation R&D management". The concept has been accepted internationally in variant forms, which in the present